Racism, climate activism, and the politics of apology: the image exclusion of Black youth activists. (December 2022) - Barnes, Brendon R.
Global heating is associated with historical and contemporary climate racism. Apologies for (climate) racism have the potential to facilitate meaningful discussions about a way forward. However, apologies are complex and can reveal assumptions about privilege. There has been very little work on understanding apologies concerning climate racism. I focus on the apologies received by three Black women activists who (separately) had their images excluded from reporting about their climate activism. The activists alleged that the acts were racist at the individual and systemic levels. I analysed the apologies, online responses, and actions to repair the damage using thematic analysis. I argue that the apologies were not meaningful. Apologies also reveal how privilege operates, including controlling the narrative, drawing on unconscious racism, silence, and ignoring victim reparations. I discuss the importance of apology expectations for climate change from countries in the global North towards the global South. I also discuss the implications for future psychological studies on climate racism.